THE EFFECT OF LEADERSHIP STYLE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT CV. MAJU SEJAHTERA INTI - Aprillia Hestina; Iskandar Ali Alam (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study aims to analyze the influence of leadership style and organizational commitment on employee performance at CV. Maju Sejahtera Inti.METHODOLOGY - The study used a quantitative survey design with all 34 employees as census sampling. Data were collected through a structured questionnaire and analyzed using SPSS version 27, including data quality testing and multiple linear regression.FINDING - The results showed that leadership style has a positive and significant effect on employee performance, indicating that the leadership's ability to provide clear direction, motivation, role model, and effective communication can improve employee performance. Organizational commitment also has a positive and significant effect, indicating that employees sense of belonging and willingness to contribute improve their performance. Simultaneously, leadership style and organizational commitment have a significant effect on employee performance, emphasizing the importance of an integrated approach